2018
DOI: 10.1021/acs.jafc.8b00489
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic Pretreatment Combined with Dry-State Glycation Reduced the Immunoglobulin E/Immunoglobulin G-Binding Ability of α-Lactalbumin Revealed by High-Resolution Mass Spectrometry

Abstract: Bovine α-lactalbumin (α-LA) is one of major food allergens in cow's milk. The present work sought to research the effects of ultrasonic pretreatment combined with dry heating-induced glycation between α-LA and galactose on the immunoglobulin E (IgE)/immunoglobulin G (IgG)-binding ability and glycation extent of α-LA, determined by inhibition enzyme-linked immunosorbent assay and high-resolution mass spectrometry, respectively. The IgE/IgG-binding ability of glycated α-LA was significantly decreased as a result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 32 publications
(57 reference statements)
3
43
0
Order By: Relevance
“…The electrophilic activity of aldose is higher than that of ketose, and the terminal group has smaller steric hindrance, which makes the amino compounds are easier to approach (Jing & Kitts, 2004). The similar conclusion was drawn in our previous study on the α‐lactalbumin ultrasonic pretreatment combined dry‐state glycation (Liu, Tu, Liu, et al, 2018). As expected, the modification degree was direct relation between the sugar size and structure, they were PV‐Rib, PV‐Gal, PV‐Glu, PV‐Fru, and PV‐Lac, respectively.…”
Section: Resultssupporting
confidence: 90%
“…The electrophilic activity of aldose is higher than that of ketose, and the terminal group has smaller steric hindrance, which makes the amino compounds are easier to approach (Jing & Kitts, 2004). The similar conclusion was drawn in our previous study on the α‐lactalbumin ultrasonic pretreatment combined dry‐state glycation (Liu, Tu, Liu, et al, 2018). As expected, the modification degree was direct relation between the sugar size and structure, they were PV‐Rib, PV‐Gal, PV‐Glu, PV‐Fru, and PV‐Lac, respectively.…”
Section: Resultssupporting
confidence: 90%
“…The milk protein‐specific IgE levels of five human antisera were 6.71, 9.977, 17.1, 43.6 and ≥100 kUA/L, respectively. Rabbit antisera were prepared by a previously reported protocol (Liu, Tu, Liu, et al., 2018).…”
Section: Methodsmentioning
confidence: 99%
“…The IgE/IgG–binding ability of α‐La, β‐Lg, N‐La‐OA, N‐Lg‐OA, U‐La‐OA, and U‐Lg‐OA was estimated by ELISA (Liu, Tu, Liu, et al., 2018). Human antisera (prepared by mixing the sera of five patients at the same volume) and rabbit antisera were applied to study the IgE/IgG–binding ability.…”
Section: Methodsmentioning
confidence: 99%
“…For this study, K79 and K93 were identified in the glycated BLA after ultrasound pretreatment (Figure b). Our earlier study shows that glycated BLA mainly occurred on Lys (Liu, Tu, Liu, et al, ). It is of interest to point out that glycated site and DSP values could be altered by conformational structure of modified BLA via ultrasound.…”
Section: Resultsmentioning
confidence: 94%
“…Bovine α‐lactalbumin (BLA), one of the model Ca 2+ binding proteins that carries out diverse functions in the food and biology, as an ingredient of the function and nutrition (Liu, Tu, Shao, et al, ) and an ingredient for infant nutrition in the food. The BLA possesses a broad range of the functional properties, such as antioxidant (Liu, Tu, Shao, et al, ), immune‐modulating (Liu, Tu, Liu, et al, ), antibacterial (Sedaghati, Ezzatpanah, Boojar, & Ebrahimi, ), or antitumor activity (Fang, Zhang, Wu, Fan, & Ren, ), and so on. Chemical and physical methods are most popular modified technology capable of improving the structural and functional properties of protein (Liu, Tu, Yang et al, ; Yang, Tu, Wang, Li, & Tian, ).…”
Section: Introductionmentioning
confidence: 99%